2023
DOI: 10.3390/antiox12040823
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation Potentiates Exercise Protective Effects against Doxorubicin-Induced Hepatotoxicity in Mice

Abstract: We tested the hypothesis that creatine supplementation may potentiate exercise’s protective effects against doxorubicin-induced hepatotoxicity. Thirty-eight Swiss mice were randomly allocated into five groups: control (C, n = 7), exercised (Ex, n = 7), treated with doxorubicin (Dox, n = 8), treated with doxorubicin and exercised (DoxEx, n = 8), and treated with doxorubicin, exercised, and supplemented with creatine (DoxExCr, n = 8). Doxorubicin was administered weekly (i.p.) for a total dose of 12 mg/kg. Creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Given that CR inherently mitigates oxidative stress, it is also likely that this reduction in CR transport and processing also allows ROS to form more freely, thereby increasing the chances of cardiac damage and cardiomyopathy development. Thus, the increase in concentration of CR through supplementation could make up for this reduced transportation rate, mitigate oxidative stress damage in the heart, and help to preserve the strength of the myocardium as well as the health of other organs [ 29 , 53 , 54 ]. Since this transportation rate reduction may be long-term, this may also indicate a need for long-term CR supplementation after successful cancer elimination, although that will require further research.…”
Section: Discussionmentioning
confidence: 99%
“…Given that CR inherently mitigates oxidative stress, it is also likely that this reduction in CR transport and processing also allows ROS to form more freely, thereby increasing the chances of cardiac damage and cardiomyopathy development. Thus, the increase in concentration of CR through supplementation could make up for this reduced transportation rate, mitigate oxidative stress damage in the heart, and help to preserve the strength of the myocardium as well as the health of other organs [ 29 , 53 , 54 ]. Since this transportation rate reduction may be long-term, this may also indicate a need for long-term CR supplementation after successful cancer elimination, although that will require further research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have shown improvements in mitochondrial function, markers of oxidative stress and inflammation [ 20 , 41 , 42 ]. Only two studies to date have evaluated the effects of exercise on AST and ALT in animals treated with DOX [ 43 , 44 ]. In these studies, 12 weeks of treadmill exercise preconditioning or 5 weeks of strength training concomitant to DOX treatment showed a reduction in circulating AST.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, 12 weeks of treadmill exercise preconditioning or 5 weeks of strength training concomitant to DOX treatment showed a reduction in circulating AST. Interestingly, ALT was only reduced with the aerobic preconditioning exercise [ 44 ], while it was increased with strength training [ 43 ]. These studies were performed in male rodents and support our findings that markers of hepatotoxicity are increased in male rodents treated with DOX.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were kept in collective cages (~4 mice/cage) with full access to food (Nuvilab ® balanced CHO pellets, Nuvital SA, Colombo, Brazil) and water, at controlled room temperature (26 ± 1°C). According to previous studies conducted in our laboratory [ 14 , 15 ], a total of seventeen mice were randomly assigned into one of two groups designated as Control (C, n = 7) and treated with doxorubicin (Dox, n = 10). The Dox group had a larger sample size due to the possibility of animal mortality.…”
Section: Methodsmentioning
confidence: 99%